Sharia Service as An Added Value: Response to Sharia Standard in Hospital Service - Maksum, Muhammad; Wahyuni, Afidah; Farida, Ade Rina; Hasanah, Latifatul; Fuad, Sahlul (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
The application of sharia principles in business activities and services adds to standard compliance and some of them are trapped in the legalistic formality aspect rather than improving business ethics. In hospitals, which main business is providing health services, applying sharia principles may enhance the added value in health services or just a formal aspect. The purpose of this study seeks to reveal the community's response to the application of sharia standards in hospitals. The study used a quantitative research method, through the distribution of questionnaires to 50 patients and their families in three regional public hospitals; Zainoel Abidin Hospital Aceh, Sultan Agung Hospital Semarang, and Bandung Islamic Hospital, and interviews with the management and sharia supervisory board of the hospital. This study describes descriptively, with a Likert scale approach, to see the response toward the application of sharia standards. The results show that the majority of respondents gave a positive response to the application of sharia standards. Sharia standards are added value services in sharia hospitals. The results of this study is implicated in the management of sharia compliance in hospitals and the need for regulatory support for the implementation of sharia in hospitals.